ATTITUDE - EFFECTS OF POPULAR POLICY (Academia Science Repository, 2023)
On March 13, 2023, the President of the Republic of Uzbekistan Shavkat Mirziyoyev visited the Surkhandarya region in order to get acquainted with the progress of socio-economic reforms in the regions. While carefully observing the process, we witnessed that the state policy reflects people's wishes and noble dreams and is becoming more and more populist. Taking into account the objections of the people about the quality of the roads in the "Boysun-Denov" direction, the head of state decided to drive a car on the Surkhandarya roads. Similar life examples are clearly visible during visits to other regions.